Global and emerging trends in tourism - Bayrakcı, Selman; Yetimoğlu, Seda; Aras, Sercan (Konya: Necmettin Erbakan Üniversitesi Yayınları, 2021)
Prepared with an interdisciplinary approach in the field of tourism, the book focuses on current issues in tourism. The book, prepared by experts in the field, includes topics such as Tourism Destination Management, Digital Marketing in Rural Tourism, Halal Tourism, Women Entrepreneurship and Tourism, Hospitality, MICE Tourism, Covid-19 Process in Tourism. We hope that the book prepared in this context will contribute to Turkish tourism with theoretical and practical scientific studies in the field of tourism. In addition, we would like to thank the authors of the chapters, who had a great share in the emergence of the book with their devoted work, and the employees of NEU Publishing House for their hard work.
1
Keywords: Ekonomi, finans ve işletme, -- Turizm sektörü; Economy, finance and business, -- Tourism industry